2011
DOI: 10.1111/j.1095-8339.2010.01103.x
|View full text |Cite
|
Sign up to set email alerts
|

Is lack of cycad (Cycadales) diversity a result of a lack of polyploidy?

Abstract: Many hypotheses exist for the relative diversity of seed plant taxa. We discuss one of them: how the relative dearth of cycad diversity throughout their 300 million year history may be a result of a lack of duplication of their entire nuclear genome, often termed polyploidy. We show theoretically how polyploidy causes speciation via cryptic reproductive isolation. Polyploidy can also cause radiations via epigenetically induced heterochrony and plasticity. Most cycads have only a few large chromosomes because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 127 publications
(143 reference statements)
1
23
0
Order By: Relevance
“…We showed that only by looking at the genome level can the functions and origins of sex be understood (Gorelick and Heng, ). We also showed that radiations in plants may largely be a result of polyploidy, aka whole genome duplication, which (antithetically, as we show below) is definitely a genetic rather than a genomic phenomenon (Gorelick and Olson, ).…”
supporting
confidence: 57%
See 1 more Smart Citation
“…We showed that only by looking at the genome level can the functions and origins of sex be understood (Gorelick and Heng, ). We also showed that radiations in plants may largely be a result of polyploidy, aka whole genome duplication, which (antithetically, as we show below) is definitely a genetic rather than a genomic phenomenon (Gorelick and Olson, ).…”
supporting
confidence: 57%
“…This not a scenario in which adaptation would ever be expected (Lynch, , ). For further discussion of how polyploidy probably causes radiations that are not adaptive see Gorelick () and Gorelick and Olson ().…”
Section: Polyploidy Causes Radiations But Is Not Adaptivementioning
confidence: 99%
“…17,22 G. biloba is one of the most notable zoidogamous gymnosperms. 23,24 Studies on the sexual reproductive process in G. biloba confirmed that when the spermatozoid is released from the pollen tube, the archegonial chamber is full of liquid, through which the spermatozoids swim. 7,17 It was thought that the liquid originated from the pollen tube, or from the degenerated nucellar tissues.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%
“…emersus to behave similarly. Hitherto polyploidy has not been reported in cycads (Gorelick & Olson 2011), making an allopolyploid origin for subsp. emersus unlikely.…”
Section: Iucn Red List Status:-inmentioning
confidence: 99%